Tác động của di cư đến mức độ tổn thương về an ninh lương thực hộ gia đình: Bằng chứng từ Việt Nam - Võ Tất, Thắng; Nguyễn Thị Bích, Hiền; Trần Mỹ, Huyền (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study investigates the relationship between migration and household vulnerability to food insecurity in Vietnam, using panel data from the Vietnam Household Living Standards Survey (VHLSS) for 2016–2018. A fixed effects model is employed to examine how different forms of migration (short-term, long-term, labor-related, and non-labor-related) affect vulnerability in the consumption of four key nutrients: energy, protein, fat, and carbohydrates. The Vulnerability as Expected Poverty (VEP) approach is adapted to measure food security vulnerability. Results show that short-term labor migration increases vulnerability, reflecting the adverse effects of labor shortages during the initial transition period. In contrast, long-term labor migration reduces vulnerability as remittances stabilize and households accumulate knowledge to improve production and consumption. Furthermore, labor-related migration has a stronger impact than non-labor-related migration in both short- and long-term cases.
Keywords: Food security; Migration; Vulnerability; Nutrition